Dynamic Patterns of Global Brain Communication Differentiate Conscious From Unconscious Patients After Severe Brain Injury - Golkowski, Daniel; Willnecker, Rebecca; Rösler, Jennifer; Ranft, Andreas; Schneider, Gerhard; Jordan, Denis; Ilg, Rüdiger (Frontiers in Systems Neuroscience, 2021)
The neurophysiology of the subjective sensation of being conscious is elusive and therefore it remains controversial how consciousness can be recognized in patients who are not responsive but seemingly awake. During general anesthesia, functional magnetic resonance imaging was able to show that the default-mode network and the attention network are important targets of anesthesia and that some patterns of global brain communication are highly specific for intact consciousness. The aim of this functional magnetic resonance imaging study was to detect such patterns in cohorts of unresponsive wakeful patients (n=18) and unmatched healthy controls (n=20) in order to evaluate their potential use in clinical practice. Patterns of global brain communication and their dynamic change were strictly associated with intact consciousness in this cohort of unresponsive patients and controls. Additionally, we show that appearance of these patterns is significantly related to activity within the frontoparietal networks of the brain thus bridging the gap between basic research and clinical application. We propose that this approach is able to recognize consciousness in the clinical routine setting in the future.